Development of PCR test system for Pyrenophora tritici-repensis detection (Experimental biology, 2020)
In recent years, there has been a noticeable expansion of the range and severity of the tan spot  in Kazakhstan. The high adaptive ability of the fungus contributes to the wide spread and increased harmfulness of the pathogen. It is quite difficult to identify the species of fungus by the symptoms of the manifestation of the disease on the leaves of plants and by the morphological features of conidia. The creation of domestic diagnostic tools to identify the causative agent of wheat tan spot  Pyrenophora tritici-repensis is an urgent task. Among molecular methods, the most convenient and operational method is PCR diagnostics. PCR makes it possible to detect fungal DNA even before physiological symptoms become visible on plant tissue.The aim of this work is to develop a PCR test system for the diagnosis of wheat tan spot. As a result of the studies, species-specific primers were selected and synthesized to identify the causative agent of wheat tan spot, the conditions for PCR formulation were optimized: the composition of the reaction mixture and the temperature and time regime. The specificity and sensitivity of the test system was determined. The developed test system showed rather high specificity and allows detection of the pathogen nucleic acid in the samples under study in the amount of 2,6 pg. This test system can be used for the rapid detection of pathogen DNA in samples. Keywords: tan spot, PCR, specificity, sensitivity, diagnosis.